Spaceborne observations of the lidar ratio of marine aerosols - K. W. Dawson; N. Meskhidze; D. Josset; S. Gassó (Atmospheric Chemistry and Physics, 2015)
Retrievals of aerosol optical depth (AOD) from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) satellite sensor require the assumption of the extinction-to-backscatter ratio, also known as the lidar ratio. This paper evaluates a new method to calculate the lidar ratio of marine aerosols using two independent sources: the AOD from the Synergized Optical Depth of Aerosols (SODA) project and the integrated attenuated backscatter from CALIOP. With this method, the particulate lidar ratio can be derived for individual CALIOP retrievals in single aerosol layer, cloud-free columns over the ocean. Global analyses are carried out using CALIOP level 2, 5 km marine aerosol layer products and the collocated SODA nighttime data from December 2007 to November 2010. The global mean lidar ratio for marine aerosols was found to be 26 sr, roughly 30% higher than the current value prescribed by the CALIOP standard retrieval algorithm. Data analysis also showed considerable spatiotemporal variability in the calculated lidar ratio over the remote oceans. The calculated marine aerosol lidar ratio is found to vary with the mean ocean surface wind speed (U10). An increase in U10 reduces the mean lidar ratio for marine regions from 32 ± 17 sr (for 0 < U10 < 4 m s−1) to 22 ± 7 sr (for U10 > 15 m s−1). Such changes in the lidar ratio are expected to have a corresponding effect on the marine AOD from CALIOP. The outcomes of this study are relevant for future improvements of the SODA and CALIOP operational product and could lead to more accurate retrievals of marine AOD.